Prevalence of Pregnancy-Induced Hypertension and Pregnancy Outcomes - Muhammad Awais Khalid, Ahmed Ejaz, Umar Arif, Tehmas Haider Jaffery, Ammarah Mahmood, Sohaib Arif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most frequent medical comorbidity during pregnancy is hypertension, rendering an elevated menace of unfavorable outcomes for equally mother and infant. It is a substantial public health concern, characterized by eclampsia, chronic hypertension, and preeclampsia. Objectives: The study determined occurrence of pregnancy-induced hypertension (PIH) and pregnancy outcomes, in the locality of Pakistan. Methods: The cross-sectional research appraised 05 districts of Pakistan in 2021-22. The study comprised 1920 patients affected with PIH. The demographic characteristics, laboratory and clinical values and pregnancy outcomes were recorded on the approved questionnaire. Results: Prevalence of PIH in pregnant females in study area was recorded as 13.70%. A significant proportion of PIH-affected females had genetic predisposition (51.14%), followed by abortion history (15.52%), history of hormonal imbalance (9.94%), history of Cesarean section (7.50%) and history of stillbirth (0.88%). Pregnancy outcome revealed that 16 (0.833%) women died of the PIH, 31 suffered from renal failure, 36 from pulmonary edema, 4.06% were affected with abruptio placentae and 103 suffered from HELLP syndrome. Similarly, the neonatal complications revealed that 27 fetuses died to mothers’ PIH, 111 suffered from asphyxia (5.78%) at the time of birth and 13 infants were abnormal and had different congenital anomalies. Practical implication: It emphasized the need for improved prenatal care, early detection of pregnancy-induced hypertension, and meticulous management of the condition in order to improve maternal and neonatal outcomes, especially in high prevalence regions such as Pakistan. Conclusion: The frequency of PIH in Pakistan was high (13.70%) and women had a greater risk of adverse pregnancy outcomes. With good prenatal care and continuous monitoring of the mother and fetus, perinatal outcomes including maternal morbidity and infant mortality can be avoided. Keywords: Asphyxia; Hypertension; Neonatal mortality; Perinatal outcomes.